Analysis of the Effectiveness and Contribution of Land and Building Rights Acquisition Fees (BPHTB) Revenue to Sukabumi City Regional Original Revenue - Dara Anisya Rahman; Susi Hambani; Ayi Jamaludin; Yuppy Triwidatin (Indonesian Journal of Advanced Research, 2023)
This study aims to determine and analyze the magnitude of the effectiveness of BPHTB Revenue in Sukabumi City and to analyze the magnitude of the contribution of BPHTB to Regional Original Income in Sukabumi City. The research design used in this research is descriptive with a quantitative approach. The data collection method used in this research was interviews. The data sources in this research use secondary data and primary data. The data used in this study are data on the realization of tax revenue from land and building rights acquisition fees and data on the realization of Regional Original Income for the City of Sukabumi from 2017 to 20221. The results show the level of effectiveness of BPHTB revenues in Sukabumi City from 2017 to 2021 as a whole. Overall, it shows that the value interpretation is very effective with an average percentage of 127.98%, which means it is very effective. Meanwhile, the contribution level of BPHTB revenues to the Local Revenue of the City of Sukabumi in 2017 to 2021 as a whole shows a very low value interpretation with an average percentage of 4.88%, which means the contribution is very less.